Intra-Group Orca Call Rate Modulation Estimation Using Compact Four Hydrophones Array - Poupard, Marion; Symonds, Helena; Spong, Paul; Glotin, Hervé (Frontiers in Marine Science, 2021)
Acoustic emissions are vital for orca (Orcinus orca) socializing, hunting, and maintaing spatial awareness. Studying the acoustic emissions of orcas on an individual basis often results in interference with their natural behaviors through mounting tags or following by boat. In order to analyze their inter- and intra-group communication, we propose a study allowing us to associate vocalizations with their emitter (matriline and when possible individual). Such a non-interfering device for allocating calls to individual orcas could substantially boost our understanding of their complex acoustic world. Our experimental protocol was based on a compact array of four hydrophones fixed near the shore, operable up to 1 km away from the path of orcas. It was used during summer 2019 at the research station OrcaLab, northern Vancouver Island, Canada. A total of 722 calls were extracted, jointly with visual identification and azimuth of surfacing orcas, allowing validation of the acoustic diarization and azimuth estimations of the orca calls. We then calculated the Call Rate (CR) for each matriline or when possible individual in order to describe their acoustic activity. Preliminary results show that CR could be modulated according to the distance of the signaler from a group, the presence of another group, or anthropic pressure.